ANALISIS MATA PENCAHARIAN DI LAHAN GAMBUT: KASUS KABUPATEN TANJUNG JABUNG BARAT - Surati Surati; Setiasih Irawanti; Dian Charity Hidayat; Handoyo Handoyo; Kuncoro Ariawan; Andri Setiadi Kurniawan; Raden Mohammad Mulyadin (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
Peatland is unique, marginal and fragile ecosystem, therefore its utilization should be based on careful research and planning, and requires support from stakeholders. The utilization of peatland by community is generally in the forms of yards, fields, and gardens. The study aims to examine community activities on peatland to be source of livelihood and income. Research was conducted in Bram Itam Raya and Mekar Jaya villages, Tanjung Jabung Barat District. Data were analyzed by using thematic, economic social dimension analysis, and SWOT analysis. The results show the activities that can be source of livelihood and income in peatland are plantation, agriculture, and other forest products while income from non-land are entrepreneurship, services and livestock.People’s livelihoods generally are plantation farmers (60.35%), with main commodities pinang, coffee, and palm oil, with average income greater than UMP namely up to Rp4,467,282.61per month. It illustrates that incomefrom peatland can fulfill their needs properly. There is limited knowledge of farmer in cultivating land, selection of plant species that can be adapted to biophysical conditions and how to cope with pests and diseases. To overcome limitation of community knowledge, it is necessary to provide alternative activities and sources of livelihood with agroforestry techniques.